2022
DOI: 10.1038/s41591-022-01714-5
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolomic profiling reveals extensive adrenal suppression due to inhaled corticosteroid therapy in asthma

Abstract: The application of large-scale metabolomic pro ling provides new opportunities to realize the potential of omics-based precision medicine with regard to asthma. We leveraged over 14,000 individuals from four distinct epidemiological studies. We identi ed and independently replicated seventeen steroid metabolites that were signi cantly reduced in individuals with prevalent asthma. Importantly steroid levels were reduced among all individuals with asthma regardless of medication use; however, the largest reducti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 74 publications
1
56
1
1
Order By: Relevance
“…For example, FF 100 µg has been previously shown to produce a 7% reduction in plasma cortisol, which although not statistically significant, is a dose-related effect [ 11 ]. Similarly, in a large metabolic profiling study by Kachroo et al [ 12 ] , a dose–effect relationship was observed with steroid metabolites including cortisol and dehydroisoandrosterone sulfate and ICS treatment. Although this reduction was primarily driven by ICS treatment, reduced steroid levels also represented a fundamental characteristic of pathophysiology of asthma [ 12 ].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…For example, FF 100 µg has been previously shown to produce a 7% reduction in plasma cortisol, which although not statistically significant, is a dose-related effect [ 11 ]. Similarly, in a large metabolic profiling study by Kachroo et al [ 12 ] , a dose–effect relationship was observed with steroid metabolites including cortisol and dehydroisoandrosterone sulfate and ICS treatment. Although this reduction was primarily driven by ICS treatment, reduced steroid levels also represented a fundamental characteristic of pathophysiology of asthma [ 12 ].…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, in a large metabolic profiling study by Kachroo et al [ 12 ] , a dose–effect relationship was observed with steroid metabolites including cortisol and dehydroisoandrosterone sulfate and ICS treatment. Although this reduction was primarily driven by ICS treatment, reduced steroid levels also represented a fundamental characteristic of pathophysiology of asthma [ 12 ]. It is important to note that cortisol suppression is not the same as adrenal suppression; nevertheless, reductions in steroid metabolites have been referred to as “adrenal insufficiency” by some authors [ 12 ], but this was without evidence via adrenocorticotropic hormone stimulation testing.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Metabolomics is a comprehensive biochemical profiling technique that is used to assess systemic metabolism in a biological sample, reflecting the “net effects” of genetic, transcriptomic, proteomic, and environmental interactions [ 5 , 6 ]. The authors of a recent study performed fecal metabolomics in infants receiving PN, in which they identified 12 sphingomyelin lipids as potential biomarkers for the development of cholestasis in combination with birth anthropometry [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The scientific dividends of the Biobank have already been substantial. For example, MGB Biobank data have been used in studies demonstrating the limitations of contemporary guidelines for managing patients at high genetic risk of coronary artery disease, to evaluate polygenetic Risk Score models for prostate cancer, and to identify extensive adrenal suppression due to inhaled coriscosteroid therapy in asthma [ 17 , 18 , 19 ]. It also provides the foundation to manage large NIH-funded research programs that require IT support that can scale and staff with large-scale recruitment and biobanking experience.…”
Section: Measuring the Value Of The Biobankmentioning
confidence: 99%